Precursor and seeding time of flint winter wheat - Ярчук, І. І.; Мельник, Т. В. (Scientific Progress & Innovations, 2018)
Ukraine has all weather conditions for producing high quality grain of flint winter wheat, but there still insufficiently clear recommendations on the technology of growing flint winter wheat in the conditions of the Northern Steppe of Ukraine. Therefore, it is necessary to study the influence of the main elements of cultivation technology to provide high-quality grain of the food industry. The results of the study of influence of the seeding rate on the crop capacity of flint winter wheat after three years of testing are presented. We described the most effective measures of a flint winter wheat seeding of sort Continent in a Northern Steppe. During the three years of research, optimum seeding time have been determined for various precursors depending on the mineral nutrition level. The largest development during the termination of autumn vegetation is acquired plants that grow after the vapor precursor at the first seeding time when using high doses of mineral fertilizers, however, such crops are characterized by a worse overwintering. The largest number of plants survived after overwintering is observed after the stern precursor and latest seeding time with increased level of mineral nutrition. After vapor precursor the highest level of surviving was detected on the plots with the latest seeding time. According to the stern precursor, the maximum crop capacity of flint winter wheat is formed while seeding September 10 with high level of mineral nutrition, and after the vapor precursor the largest crop capacity is given by plants that was sown September 17 with a high level of mineral nutrition. The highest yield was formed after the vapor precursor at a high level of mineral nutrition at the sowing on September 17 and amounted to 3.68 t/ha.